The crisis is over, long live the crisis: mental health in emerging adulthood during the course of the COVID-19 pandemic - Wirkner, Janine; Brakemeier, Eva-Lotta (Frontiers in Psychology, 2024)
As a multidimensional stressor, the COVID-19 pandemic posed a significant threat to mental health, with studies showing younger age groups to be particularly vulnerable. Thus, this study aimed to monitor mental health, potential risk/protective factors, and pandemic-related variables among young university students during the pandemic. Students of the University of Greifswald (M age=23.0 years, 73.9% female) participated in five cross-sectional online surveys in December 2020 (N=1127), March 2021 (N=760), June/July 2021 (N=531), December 2021 (N=1226), and December 2022 (N=814). Sociodemographic data, depression and anxiety severity, loneliness, quality of life, coping strategies, resilience, self-esteem, and emotion regulation were measured. First, results from December 2020 were compared to pre-pandemic normative data. Second, the time course during the pandemic was analyzed. Third, linear models were calculated to examine the influence of risk and protective factures on depression and anxiety severity. Higher levels of depression, anxiety, and loneliness, as well as lower levels of self-esteem, physical and mental health, social relationships and well-being were found in December 2020 compared to pre-pandemic. Levels of depression and anxiety severity peaked in December 2022. Female sex, loneliness, and previous mental treatment showed associations with higher depression and anxiety severity, while higher self-esteem, resilience and use of reappraisal strategies appeared to act as protective factors. The study indicates the pandemic's detrimental impact on students' mental health and quality of life. Identified risk and protective factors provide guidance for tailored prevention and treatment, as well as the design of measures for future pandemics and other crisis.